Serviceability of Post-fire RC Rafters with Openings of Different Sizes and Shapes (Journal of Engineering, 2022)
This study deals with the serviceability of reinforced concrete solid and perforated rafters with openings of different shapes and sizes based on an experimental study that includes 12 post-fire non-prismatic reinforced concrete beams (solid and perforated). Three groups were formed based on heating temperature (room temperature, 400 °C, and 700 °C), each group consisting of four rafters (solid, rafters with 6 and 8 trapezoidal openings, and rafter with eight circular openings) under static loading. A developed unified calculation technique for deflection and crack widths under static loading at the service stage has been provided, which comprises non-prismatic beams with or without opening exposed to flexure concentrated force. Two approaches were used to compute the deflection: The first attempt was conducted by using the moment of inertia for solid non-prismatic beam and reduced for those with openings by the ratio of residual rafter self-weight. The second was performed by using the moment of inertia of transformed cracked sections depending on the segmental rafter method. The crack width was determined using the ACI code's equation. The analytical and experimental results were evaluated and found to be in good agreement.